Establishingdiagram of absolute crustal movements in Vietnam using GNSS data - Hai, Vy Quoc; Tham, Bui Thi Hong (Vietnam Journal of Earth Sciences, 2015)
International Terrestrial Reference Frame (ITRF) is created under the auspices of international to satisfy stringent standards of modern space systems. Basic feature of ITRF is the time factor. Thus coordinates and velocities of points are changing in ITRFyy-s. With the mission to link with international networks or study crustal movements, diagram of velocity movements plays an important role. This paper presentstheoretical background, basic formulas and method for calculating absolute velocity transferral between different ITRF. The overall picture of absolute crustal movements on the territory of Vietnam in the only one international coordinate system and latest ITRF08 has been established and discussed. The calculation is performed in accordance with strict accuracy and reliability. This method enables continuous integration of new results and update instantly the picture of crustal movements in Vietnam, guaranteed accuracy, and cost- and time- save.ReferencesVy Quốc Hải, 2009: Xác định chuyển dịch tuyệt đối khu vực lưới GPS Tam Đảo-Ba Vì. Tạp chí Địa chất. T.311, (3-4), tr.22-30. Vy Quốc Hải, Bùi Thị Hồng Thắm, Dương Chí Công, 2012: Tính chuyển vận tốc chuyển dịch tuyệt đối giữa các khung quy chiếu Trái Đất quốc tế (ITRF). Hội nghị khoa học lần thứ 20. Trường Đại học Mỏ-Địa chất. Christopher Jekeli, 2012: Geometric Reference Systems in Geodesy. Ohio State University. Lê Huy Minh, Kurt Feigl, Frédéric Masson, Dương Chí Công, Alain Bourdillon, Patrick Lasudrie Duchesne, Nguyễn Chiến Thắng, Nguyễn Hà Thành, Trần Ngọc Nam, Hoàng Thái Lan, 2010: Dịch chuyển vỏ Trái Đất theo số liệu GPS liên tục tại Việt Nam và khu vực Đông Nam Á. Tạp chí các khoa học về Trái Đất, T.32, 3, tr.249-260. T. Soler, J.Y. Han, N.D. Weston, 2011: Alternative transformation from Cartesian to geodetic coordinates by least squares for GPS georeferencing applications. Computers & Geosciences, pp.100-109. Bùi Thị Hồng Thắm, 2014: Nghiên cứu cơ sở lý thuyết cho việc hiện đại hóa lưới khống chế trắc địa quốc gia ở Việt Nam bằng hệ thống vệ tinh dẫn đường toàn cầu GNSS. Luận án Tiến sĩ. Trường Đại học Mỏ-Địa chất. Tran Dinh To, Nguyen Trong Yem, Duong Chi Cong, Vy Quoc Hai, Zuchiewicz Witold, Cuong Nguyen Quoc, Nghia Nguyen Viet, 2013: Recent crustal movements of northern Vietnam from GPS data. Journal of Geodynamics, September 9. Phan Trọng Trịnh, Ngô Văn Liêm, Trần Đình Tô, Vy Quốc Hải, Nguyễn Văn Hướng, Hoàng Quang Vinh, Bùi Văn Thơm, Nguyễn Quang Xuyên, Nguyễn Viết Thuận, Bùi Thị Thảo, 2011: Tốc độ chuyển động kiến tạo hiện đại trên Biển Đông và khu cực lân cận theo chu kỳ đo GPS 2009-2010. Tạp chí Khoa học và Công nghệ Biển, 1, tr. 15-30. Bureau International des Poids et Mesures (BIPM) and US Naval Observatory (USNO), 2010: IERS Conventions. http://www.geologie.ens.fr/~vigny/geod03.html: GEODYSSEA GPS Results.